Renewing professional librarianship : C. A. Augustine festschrift - Devarajan, G. (New Delhi : Ess Ess, 1991)
"Can professional librarianship exist, let alone thrive, in the 21st century? Does accreditation protect the profession, or reduce it to a minor component of information science? The prognosis is not good, claims cultural pragmatist Bill Crowley, with worse to follow unless library studies and information studies are viewed as separate cognate areas." "While an information-centric definition may be appropriate for corporate information specialists, academic, public, and school librarians are already suffering the effects of devaluation. The remedy, Crowley says, is to embrace a concept called lifecycle librarianship, the ability to meet crucial public needs "from the lapsit to the nursing home," by honing the library's time-honored role as a vital resource for reading and lifelong learning."
"Renewing Professional Librarianship concludes with a series of recommendations for library associations, library and information education educators, and practitioners - and a challenge for the reader to do something with them!"--Back cover.
Introduction -- Librarian professionalism and professional library education -- "What's the story?" -- The information-library conundrum -- The ebbing of information science -- Restoring the balance.
Includes bibliographical references (p. [155]-165) and index.
Keywords: Library science -- United States; Library science -- Canada; Library education; Library schools -- Accreditation; Librarians -- Certification; Libraries -- Aims and objectives